2020
DOI: 10.1021/acssensors.0c01769
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Gas Sensor Response of a Vertical Zinc Oxide Nanorod-Gold Junction Diode at Room Temperature

Abstract: Conventional metal oxide semiconductor (MOS) gas sensors have been investigated for decades to protect our life and property. However, the traditional devices can hardly fulfil the requirements of our fast developing mobile society, because the high operating temperatures greatly limit their applications in battery-loaded portable systems that can only drive devices with low power consumption. As ammonia is gaining importance in the production and storage of hydrogen, there is an increasing demand for energy-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 55 publications
0
41
0
Order By: Relevance
“…In the literature, today’s gas sensors have a power consumption in the µW range, but research aims for nW power consumption in the future. The power consumption when compared to other low power ammonia sensors reported in literature 33 – 38 showed that it is equivalent and three orders of magnitude lower than a commercial FIGARO ammonia sensor TGS826. The sensor performance for the gas sensors in this article is reported in terms of gas sensor response ( S ).…”
Section: Resultsmentioning
confidence: 79%
“…In the literature, today’s gas sensors have a power consumption in the µW range, but research aims for nW power consumption in the future. The power consumption when compared to other low power ammonia sensors reported in literature 33 – 38 showed that it is equivalent and three orders of magnitude lower than a commercial FIGARO ammonia sensor TGS826. The sensor performance for the gas sensors in this article is reported in terms of gas sensor response ( S ).…”
Section: Resultsmentioning
confidence: 79%
“…First, due to the spillover effect of Au toward oxygen, the addition of Au NPs can further enhance the influence of oxygen on the sensing process. 54 In addition, Au likely acts as a "carrier storage box" on the surface of InSe, which makes it possible to achieve favorable responses toward NO 2 and NH 3 by controlling light illumination. Briefly, Au NPs can store electrons of InSe under dark conditions (p-type doping effect).…”
Section: R R Qv Kt Expmentioning
confidence: 99%
“…There are several reports of the use of ZnO in sensing applications, including gas sensors, , ultraviolet (UV) sensors, ,, and pressure sensors . Moreover, ZnO is used in applications related to its photocatalytic activity. , In the area of nanomaterials-based glucose sensors, there are several reports of the use of ZnO nanomaterials and hybrid nanostructures containing this metal oxide in enzymatic glucose sensors and nonenzymatic sensors, whether amperometric or optical. ,, …”
Section: Introductionmentioning
confidence: 99%